2012
DOI: 10.1063/1.3699061
|View full text |Cite
|
Sign up to set email alerts
|

Chemical order and crystallographic texture of FePd:Cu thin alloy films

Abstract: FePd thin films have been recently considered as promising material for high-density magnetic storage devices. However, it is necessary to find a proper method of fabrication for the (001)-textured and chemically well-ordered alloy. In this paper, we present the detailed investigations of lattice parameters, chemical order degree, grain sizes and crystallographic texture, carried out on FePd alloys with 10 at.% of Cu addition. The initial [Cu(0.2 nm)/Fe(0.9 nm)/Pd(1.1 nm)]x5 multilayers were thermally evaporat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…[12] The same authors reported, that for well-ordered FePd alloys Cu admixture causes decrease of c value with simultaneous increase of a value, in comparison to the bulk values.…”
Section: Crystallographic Structurementioning
confidence: 90%
See 3 more Smart Citations
“…[12] The same authors reported, that for well-ordered FePd alloys Cu admixture causes decrease of c value with simultaneous increase of a value, in comparison to the bulk values.…”
Section: Crystallographic Structurementioning
confidence: 90%
“…Our previous studies showed, that FePdCu thin alloy films on Si(100) substrate revealed the fiber texture of [111] and [001] crystallites. [12] It manifested in the cylindrical symmetry of grains oriented around the axis normal to film plane. Therefore, the result of ω-scan did not depend on the polar angle at which the sample was placed with respect to the incident X-ray beam.…”
Section: Crystallographic Structurementioning
confidence: 99%
See 2 more Smart Citations
“…For calculating the chemical ordering parameter S of the films, the intensity of the (001) and (002) peaks is measured. S may be calculated by the following formula : S0.85thinmathspace(I001I002thinmathspace)1/2, where I 001 and I 002 are the integrated intensities of the corresponding XRD peaks, calculated from least‐squares pseudo‐Voigt fitting . The deconvolution of the mixed (200) and (002) peak yields the integrated area of the L1 0 (002) peak (for more details see Supporting Information).…”
Section: Resultsmentioning
confidence: 99%